2017
DOI: 10.1002/dneu.22544
|View full text |Cite
|
Sign up to set email alerts
|

Sonic hedgehog antagonists reduce size and alter patterning of the frog inner ear

Abstract: Sonic Hedgehog (Shh) signaling plays a major role in vertebrate development, from regulation of proliferation to the patterning of various organs. In amniotes, Shh affects dorsoventral patterning in the inner ear but affects anteroposterior patterning in teleosts. Currently, it remains unknown the function of Shh in inner ear development in terms of how morphogenesis changes in the sarcopterygian/tetrapod lineage coincide with the evolution of limbs and novel auditory organs in the ear. In this study we used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 64 publications
1
6
0
Order By: Relevance
“…To further verify the above results, titrated concentrations of Shh protein were used, and the number and diameter of spheres both increased as the concentration of Shh protein increased (Figures 1E,F ). Moreover, another two Hedgehog signaling inhibitors, SANT-1 and vismodegib (Zarei et al, 2017 ), were used to further confirm the effects of Hedgehog inhibition, and the results were consistent with above data (Figure 1E ). These results demonstrated that activation of Hedgehog signaling significantly promoted the cell proliferation and clone-forming ability of postnatal Lgr5+ progenitors and that inhibition of Hedgehog signaling significantly decreased the proliferative ability of Lgr5+ progenitor cells.…”
Section: Resultssupporting
confidence: 81%
“…To further verify the above results, titrated concentrations of Shh protein were used, and the number and diameter of spheres both increased as the concentration of Shh protein increased (Figures 1E,F ). Moreover, another two Hedgehog signaling inhibitors, SANT-1 and vismodegib (Zarei et al, 2017 ), were used to further confirm the effects of Hedgehog inhibition, and the results were consistent with above data (Figure 1E ). These results demonstrated that activation of Hedgehog signaling significantly promoted the cell proliferation and clone-forming ability of postnatal Lgr5+ progenitors and that inhibition of Hedgehog signaling significantly decreased the proliferative ability of Lgr5+ progenitor cells.…”
Section: Resultssupporting
confidence: 81%
“…A model of MB was developed that uses the Atoh1 ‐cre transgene 8 to recombine a floxed stop codon, resulting in expression of constitutively active Smo that reliably develop tumors. These tumors resemble the human sonic hedgehog (Shh)‐dependent MB 30,46,47 by enhancing Shh‐mediated proliferation 48 . Two bHLH transcription factors, Atoh1 and Neurod1, play essential roles in the proliferation and differentiation of granule cell precursors, the cellular source of MB.…”
Section: Resultsmentioning
confidence: 99%
“…These tumors resemble the human sonic hedgehog (Shh)-dependent MB 30,46,47 by enhancing Shhmediated proliferation. 48 Two bHLH transcription factors, Atoh1 and Neurod1, play essential roles in the proliferation and differentiation of granule cell precursors, the cellular source of MB. Atoh1 regulates Shh signaling in granule cell precursors in the external granule cell layer (EGL) and result in MB formation in the cerebellum.…”
Section: Neurod1 Effects On Human Schwannomamentioning
confidence: 99%
“…Besides, pax2a was also expressed in the otic region in zebrafish embryo [37]. In addition, as transcription factors/ cofactor or components of signaling transduction, these five genes have ever been reported involving otic morphogenesis through patterning and segmentation [38][39][40][41][42][43]. Specially, zebrafish pax2a was essential for hair cell development [44,45].…”
Section: The Voltage-gatedmentioning
confidence: 99%